PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PAPER ROLL HWS - John, Eddy (Jurnal Ekonomi : Journal of Economic, 2017)
This study aims to discover, develop and test the truth of a knowledge. Specifically, this research aims to analyze the influence of the product on purchasing decision of HWS paper roll, to analyze the influence of price on purchasing decision of HWS paper roll, to analyze the influence of distribution on purchasing decision of HWS paper roll to analyze promotion effect to purchasing decision of paper roll HWS In this research, the calculation is validity and reliability test, followed by assumption test analysis consisting of normality, multicollinearity and hetroskedasticity test and finally followed by regression test. From the calculation result, it is known that there is influence of product, price, distribution and joint promotion of purchasing decisions either partially or simultaneously. From the calculation results are known from the four marketing mix variables, product variables that have the greatest influence on purchasing decisions HWS productsÂ Keywords: marketing mix, purchase decision